Adaptation of Post-fortress Buildings as an Enrichment of the Functional Programme of a Housing Estate on the Example of Fort VIII Służew in Warsaw - Gleń, Piotr; Hołownia, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article refers to the problem of adaptation of post-fortress objects from the 19th century located in the strict urban tissue in Poland. The authors of the text analyse the example of adaptation of Fort VIII Służew in Warsaw as a way of making common spaces in housing estates more attractive. The rapid demilitarisation of fortresses from this period caused by the development of the art of war and the subsequent dynamic development of urban planning after the Second World War resulted in the degradation and disappearance of these valuable monuments. The Russian ring fortress of Warsaw is now entirely within the urban fabric.
Keywords: adaptation; fortification; heritage; new use function; revitalisation